Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.